2010
DOI: 10.1177/0013161x10387590
|View full text |Cite
|
Sign up to set email alerts
|

Using School Mission Statements for Reflection and Research

Abstract: Purpose: Efforts to compare schools nationally tend to focus on educational outcomes (e.g., test scores), yet such an approach assumes that schools are homogeneous with regard to their overall purpose. In fact, few studies have attempted to systematically compare schools with regard to their primary aims or mission. The present study attempts to fill this gap by exploring the utility of school mission statements as a data source for comparing and systematically reflecting on the core purposes of schools nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
100
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(103 citation statements)
references
References 7 publications
2
100
1
Order By: Relevance
“…Today mission statements are deemed an integral part of any institutional strategic planning process, representing a "vision" for their future (Carruthers and Lott 1981;Martin 1985). Business communication researchers have described mission statements as persuasive communication devices (Williams 2008), while others document a belief that the process of developing a mission statement fosters communication and commitment to a shared organizational purpose (Stemler et al 2011). After having found a place and being taken-up in earnest in the institutional organization of higher education (Barnett 1992;Birnbaum 2000;Keller 1983;Lake and Mrozinski 2011;Kuenssberg 2011;Ö zdem 2011), mission statements have, as a natural form of progression, trickled down the educational ladder and now primary-and even pre-primary-educational institutions have earnestly embraced them.…”
Section: Mission Statementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Today mission statements are deemed an integral part of any institutional strategic planning process, representing a "vision" for their future (Carruthers and Lott 1981;Martin 1985). Business communication researchers have described mission statements as persuasive communication devices (Williams 2008), while others document a belief that the process of developing a mission statement fosters communication and commitment to a shared organizational purpose (Stemler et al 2011). After having found a place and being taken-up in earnest in the institutional organization of higher education (Barnett 1992;Birnbaum 2000;Keller 1983;Lake and Mrozinski 2011;Kuenssberg 2011;Ö zdem 2011), mission statements have, as a natural form of progression, trickled down the educational ladder and now primary-and even pre-primary-educational institutions have earnestly embraced them.…”
Section: Mission Statementsmentioning
confidence: 99%
“…Yet, while it has been argued that mission statements provide "an accessible and meaningful window for further exploration of the purpose of the school" (Stemler and Bebell 2012, p. 23), they have generally been ignored as a source of empirical research data (Stemler et al 2011) other than in the field of higher education (Morphew and Hartley 2006;Eitel 1987;Fugazzotto 2009). There is a dearth of literature pertaining to the topic at the primary level, and an even greater paucity available in relation to the use and importance of mission statements in education in the Japanese and, particularly more so, New Zealand context.…”
Section: Mission Statementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, a professional development vision statement should be develop to analyze if professional develop opportunities align with the diversity needs of the building (Kose, 2009;Stemler et al, 2011).…”
Section: Recommendation For School Leaders' Practicementioning
confidence: 99%
“…A culturally relevant principal makes students' culture part of the school vision because "culture strongly influences the attitudes, values, and behaviors that students and teachers bring to the instructional process, it has to likewise be a major determinant of how the problems of underachievement are solved" (Gay, 2002, p. 114). Stemler, Bebell, and Sonnabend (2011) found that principals perceive mission statements as an essential tool to develop practice and communicate core values to teachers, students, and community. So a principal dedicated to their students' culture and the expectation that teachers use their students' cultures are a resource will make it part of their person belief system and the school's mission statement.…”
Section: Recommendation For School Leaders' Practicementioning
confidence: 99%